2017
DOI: 10.47566/2017_syv30_1-010006
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the surface of healthy and fluorotic human enamel using microhardness test

Abstract: The microhardness is an essential property of tooth enamel; there may be many factors that alter or diminish this quality causing weakness, one of which is dental fluorosis. The aim of this study was evaluate the surface microhardness of fluorotic enamel compared with healthy enamel. Two hundred forty extracted human molars were classified into four groups: Healthy (H), mild (MI), moderate (MO) and severe (S) fluorosis according to the Dean index. All samples were analyzed by Micro Vickers Hardness Tester. Ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
1
0
0
Order By: Relevance
“…A study that analyzed the microhardness of the surface of healthy and fluorotic enamel found results comparable to ours but slightly inferiors, unlike in our study they observed intact enamel and posterior teeth (28).…”
Section: Discussionsupporting
confidence: 58%
“…A study that analyzed the microhardness of the surface of healthy and fluorotic enamel found results comparable to ours but slightly inferiors, unlike in our study they observed intact enamel and posterior teeth (28).…”
Section: Discussionsupporting
confidence: 58%